Penerapan Metode Yanbu’a dalam Pembelajaran Membaca Al-qur’an di Taman Pendidikan Qur’an (TPQ) MIFTAHUL HUDA Desa Asrikaton Kabupaten Malang - Yulianti, Eny; Praminto, Yusa Linda Qotru Nada; Sya’baniah, Khalda; Rohmad, Azzufa Nurkamila; Chilmy, Mochammad Sholla Nadhif (JRCE (Journal of Research on Community Engagement), 2024)
The Yanbu'a method has been implemented in the Al-Qur'an education system at TPQ Miftahul Huda, located in Asrikaton Village, Malang Regency. The Yanbu'a instruction takes place daily in two sessions, imparting lessons in reading, writing, reciting the Al-Qur'an with tajweed (correct pronunciation), as well as memorizing hadiths. Challenges arise among novice students who tend to lack focus, compounded by insufficient parental support. The adopted solution involves enhancing interaction between parents and educators, while also introducing alternative, engaging teaching methods and providing adequate facilities.